Solid soap preparation formulation from sea grapes (Caulerpa racemosa) ethanol extract - Mariany Juwita Turnip; Rini Yanuarti; In Rahmi Fitria Fajar (Jurnal Perikanan Terpadu, 2026)
Seaweed is a macroalgae that grows abundantly in coastal waters. The content of active ingredients such as antibacterials, antioxidants are found in seaweed. One of the potential bioactive compounds found in seaweed is widely used as raw materials for cosmetics. This study aims to obtain the best formulation of solid soap from ethanol extract of sea grapes (C. racemosa). The stages in this study are the manufacture of sea grape extract, bar soap formulation, and physical evaluation of bar soap which includes organoleptic, pH, foam stability, free alkali content, unsaponifiable fat, antioxidant activity. The results of organoleptic observations of all formulations form a solid soap preparation and have the aroma of aqua fresh fragrance oil, the color of the preparation shows a green to dark green color. The pH value of the preparation has a value between 9.00-9.88. The stability value between 61.54% - 65.87%, this value meets the criteria for good foam stability. The free alkali content shows a value between 0.02%-0.08%. The highest unsaponifiable fat content was found in Rq4 (0.44%) while Rq2 had the lowest unsaponifiable fat content (0.29%). The antioxidant activity of each solid soap formulation added with sea grape (C. racemosa) ethanol extract produced an IC50 value of 176.4 ppm (Formula Rq2); 169.6 ppm (Formula Rq3), 159.3 ppm (Formula Rq4). These results indicate that the solid soap formulation that has the highest antioxidant activity is in formula Rq4 (159.3 ppm). Based on these results, it is stated that formulation Rq4 is the best formulation based on the results of physical and antioxidant evaluation tests.